2015
DOI: 10.1177/2050640615581732
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Efficacy and safety of POEM for achalasia

Abstract: Background: Peroral endoscopic esophageal myotomy (POEM) represents a less invasive alternative, as compared with conventional laparoscopic Heller myotomy for treating achalasia patients. In the last years, a number of prospective and retrospective experiences with POEM use for achalasia have been published. Methods: Relevant publications in which patients affected by achalasia underwent POEM treatment were identified by PubMed databases for the period 2010 -2013. From each study, we extracted the number and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 53 publications
(68 reference statements)
4
55
0
1
Order By: Relevance
“…The risk factors for major adverse events were short experience with the technique (<1 year), air insufflation, and mucosal edema. The results of this study are consistent with those reported in the literature [3,4,31]; also, this study confirmed that the use of CO 2 dramatically decreases the risk of complications.…”
Section: Overall Major Adverse Eventssupporting
confidence: 95%
See 3 more Smart Citations
“…The risk factors for major adverse events were short experience with the technique (<1 year), air insufflation, and mucosal edema. The results of this study are consistent with those reported in the literature [3,4,31]; also, this study confirmed that the use of CO 2 dramatically decreases the risk of complications.…”
Section: Overall Major Adverse Eventssupporting
confidence: 95%
“…Mucosal injuries have been reported during POEM in 0.3%e9% of the cases and mostly in early studies, as reported by two recent reviews [2,3]. Mucosal injuries represent the most feared type of complication, due to a hypothetic risk of fistulas, mediastinitis or peritonitis, especially when occurring in the EJ junction or cardia, areas in which these injuries are considered as authentic perforations.…”
Section: Mucosal Perforations/leakagementioning
confidence: 92%
See 2 more Smart Citations
“…The safety profile of POEM is presumed to be at least comparable to LHM or PD 10 11. In a large retrospective analysis of 1680 patients over 5 years, only 55 patients (3.3%) experienced major adverse incidents (mAEs) including delayed mucosal barrier failure (0.8%), delayed bleeding (0.2%), hydrothorax (0.5%) and pneumothorax (1.5%).…”
Section: Recent Developments In Therapy: Per-oral Endoscopic Myotomymentioning
confidence: 99%